A Highly Efficient Multifunctional Wind Barrier Based on PVDF for Power Generation in the Qinghai–Tibet Railway. Issue 3 (24th December 2021) - Wu, Hao; Cao, Hao; Jia, Changyuan; Azam, Ali; Luo, Dabing; Pan, Yajia; Zhang, Zutao
Abstract : The Qinghai–Tibet railway is the highest altitude railway globally, and monitoring and maintenance are essential parameters to obtain dynamic structural and environmental information in dangerous areas. Wind barriers are usually used to protect the safe operation of trains at high wind speeds. The power supply for monitoring gadgets is an urgent problem for high hill areas. This article presents a novel and renewable wind barrier for harvesting wind energy. The system architecture includes four main components: 1) the crosswind input module, 2) the vortex shedding occurrence module, 3) the power generation module, and 4) the energy storage and wind load reduction module. Based on the experiments, under the maximum critical wind speed (17 m s −1 ), the 13.607 V open‐circuit voltage is recorded in a single wind barrier unit with a maximum power of 31.47 μW. The output power is sufficient for charging a 47 μF capacitor to 2.21 V within 50 s. The practicability of the proposed wind barrier for harvesting wind energy is proposed for renewable energy in the Qinghai–Tibet railway. Abstract : The article proposes a highly efficient multifunctional wind barrier (MFWB)‐based polyvinylidene fluoride for power generation in the Qinghai–Tibet railway. The general architecture of the MFWB comprises four main parts: 1) the crosswind input module, 2) the vortex shedding occurrence module, 3) the power generation module, and 4) the energy storage and wind load reduction module.